MARKETING STRATEGY PLANNING BASED ON POSITIONING TO IMPROVE THE NUMBER OF STUDENTS - Astuti, Marisa; Haizam Mohd Saudi, Mohd; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
One important factor in marketing success is that the implementation of the strategy is right on target, one of which is to perform positioning. This study aims to determine the position of the Faculty of Visual Communication Design, University Widyatama, compared with five other private universities that also have a similar faculty based on the perception that high school students and propose a marketing strategy of the Faculty of Visual Communication Design, University Widyatama, to increase the number of students. The method used is the descriptive method by comparing the five universities in Bandung based on the results of the search. Believes in salient capital. The author uses seven dimensions to measure the perception of high school students in Bandung taken under the search results salient Believes capital. Respondents used were as many as 100 students in grade 3 scattered in various high schools in Bandung. The results showed that the University Widyatama positioned similar to the National Institute of Technology. Both are relatively close together, so it can be said to be strict in competing for new students. Based on the value of the Euclidean Distance Faculty of Visual Communication Design, University Widyatama should improve the quality of education, facilities, faculty, and graduate outcomes. Based on the expected marketing komunukasi Visual Design Faculty, University Widyatama can be designed with a more targeted and effective approach.